Demystifying O-GlcNAcylation: hints from peptide substrates. (22nd March 2018) - Shi, Jie; Ruijtenbeek, Rob; Pieters, Roland J
Abstract: O -GlcNAcylation, analogous to phosphorylation, is an essential post-translational modification of proteins at Ser/Thr residues with a single β- N -acetylglucosamine moiety. This dynamic protein modification regulates many fundamental cellular processes and its deregulation has been linked to chronic diseases such as cancer, diabetes and neurodegenerative disorders. Reversible attachment and removal of O -GlcNAc is governed only by O -GlcNAc transferase and O -GlcNAcase, respectively. Peptide substrates, derived from natural O -GlcNAcylation targets, function in the catalytic cores of these two enzymes by maintaining interactions between enzyme and substrate, which makes them ideal models for the study of O -GlcNAcylation and deglycosylation. These peptides provide valuable tools for a deeper understanding of O -GlcNAc processing enzymes. By taking advantage of peptide chemistry, recent progress in the study of activity and regulatory mechanisms of these two enzymes has advanced our understanding of their fundamental specificities as well as their potential as therapeutic targets. Hence, this review summarizes the recent achievements on this modification studied at the peptide level, focusing on enzyme activity, enzyme specificity, direct function, site-specific antibodies and peptide substrate-inspired inhibitors.